Investigation of brick using clay and fly ASH - Mohammed Abdirashid, Abdulkadir (2019)
Disposal of industrial waste material in to landfill has become serious an environmental issue. On other hand, consumption of natural resources due to manufacturing of conventional brick is considered hazard for our ecosystem. In order to overcome this issue, many studies have been conducted to reuse waste materials incorporating with natural resources as construction material into various filed such as civil engineering. The purpose of this study is to investigate possibility of using earthen material clay incorporating with fly-ash (by waste product of coal) for producing sustainable brick, and also the study aimed to determine engineering properties of clay bricks incorporating with fly-ash such as compressive and flexural strength test and water absorption test. The main variable of the study is fly-ash and its different replacing ratio are (0%, 20%, 30%, 40%, 50%. 60%). The fly-ash that used this study was obtain from Port Dickson Power Plant, Negeri Sembilan. However, results from laboratory showed that clay bricks incorporating up to 20% of fly-ash at 28 days of age curing present the highest compressive strength, which is 20.3MPa compared to all other mixes. Meanwhile, water absorption test presented that moisture content of clay bricks incorporating with fly-ash increase with increased of fly-ash percentages. Therefore, the findings of this study suggests that clay bricks incorporating up to 20% of fly-ash can be considerable as the optimum fly-ash content for producing more sustainable bricks which is leading to economical solution.